A jeles humanista gondolkodó és kodifikátor, Andrés Bello és a magánjogi (polgári jogi és kereskedelmi jogi) kodifikáció Chilében - Hamza, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
The author of this article analyzes the process of codificaton of private law (civil law and commercial law) in the light of the thought of Andrés Bello (1781–1865), the humanist thinker and expert of codification in Chile. The intellectual background of Andrés Bello, born in Venezuela, comprised history, philosophy, linguistics, literature, mainly poetry, education as well as law. It also deserves to be mentioned that Bello was the first rector of the State University of Chile founded in 1842. According to the idea of Andrés Bello Roman law (ius Romanum or ius civile) constituted the background of legal education as well as the primary source of the codification of private law in Chile. The author of the study points out that Bello had no legal education. In the field of philosophy he was substantially influenced by the scholastic tradition. In his works he put special emphasis on morality in compliance with the plurisecular tradition deeply rooted in natural law (derecho natural). This article provides also an insight into the partial influence of the German Historical School of Law (Historische Rechtsschule) on the law related ideas of Andrés Bello. The author emphasizes the decisive influence of Johann Gottlieb Heineccius on Andrés Bello. Andrés Bello was regarded as a major authority regarding his principles of international public law both in Europe and in most countries of Latin America. He spent 19 years in the United Kingdom, in London. His work Principios de Derecho de Gentes, published in 1832 was with no doubt fundamental in particular as far as sovereignty of State was concerned. Andrés Bello was a committed advocate of the Solidaridad americana pointing out the specific features i.e. characteristics of the Spanish speaking states in America. In the field of the codification of private law (civil law and commercial law) in Chile the role of Andrés Bello was determinant. The first step towards codification was the consolidation of the law of the country. The process of consolidation ended in 1833 when the first constitution of Chile was promulgated and came into effect. During the second period, encompassing the period between 1834 and 1838, Andrés Bello took into consideration the French Civil Code, the Austrian General Civil Code and the Civil Code of canton Bern (Switzerland) prepared by Samuel Ludwig Schnell. During the third period (from 1838 through 1849) Andrés Bello contemplated the structure and the contents of the draft Civil Code of Chile. It has to be notes that on the territory of Chile several compilations, namely the Breviarium Alaricianum, the Fuero Juzgo, the Fuero Real, the Siete Partidas, as well as the Ordenamiento de Alcalá were implemented. Moreover, the Nueva Recopilación, promulgated in 1567, the Recopilación de las Leyes de las Indias, promulgated in 1680 as well as the Novísima Recopilación, promulgated in 1805 were in effect. The author of the article emphasizes that the Civil Code of Chile prepared by Andrés Bello influenced the codification of civil law in most countries of Latin America. Therefore, as the author puts it, Andrés Bello can be regarded as a ‘father of codification of civil law’ in Latin America. The Civil Code of Chile was completed in 1855 and promulgated by the National Congress in the following year. The Civil Code of Andrés Bello came into effect in 1857. The Code is still in effect, with minor amendments i.e. modifications. The Civil Code of Chile follows partly the French Civil Code. However, the Código de la República de Chile, albeit does not contain a General Part (parte general), differs from the French model regarding its structure. Compiling the Code, Andrés Bello took into consideration the Spanish legal dogmatics based mainly on Roman law traditions (acervo jurídico romano). He also availed himself of the doctrine developed by the representatives of the German Pandectist Legal Science with particular regard to the thoughts of Friedrich Carl von Savigny (1779–1861). Several legal institutions regulated in the text of the Civil Code of Chile testifies the influence of the works of Jean Domat (1625–1696), Robert-Joseph Pothier (1699–1772), Merlin, Favard de Langlande, Jean-Etienne-Marie Portalis ((1745–1807), Raymond Théodore Troplong, Pardessus and Carl Salomo Zachariae von Lingenthal (1769–1843). Andrés Bello took into consideration first of all the French Civil Code, the Austrian General Civil Code (Allgemeines Bürgerliches Gesetzbuch, ABGB), the Louisiana Civil Code, the Prussian General Land Code (Allgememeines Landrecht) as well as the Dutch Civil Code (Burgerlijk Wetboek), promulgated in 1838. In the last part of his study the author emphasizes that the Civil Code of Chile does not contain a General Part (Parte General). The structure of the Civil Code of Chile is as follows: the Preliminary Title (Titulo preliminar), containing general dispositions, the Law of Persons, the Rights In Rem, The Law of Succession (Law of Inheritance) and the Law of Contractual Obligations.